Dynamical models of acute respiratory illness caused by human adenovirus on campus - Zhang, Wei; Ma, Xia; Zhang, Yongxin; Luo, Xiaofeng (Frontiers in Physics, 2022)
Acute respiratory illness caused by human adenovirus have been increasing in morbidity and mortality in recent years. Currently, isolation of symptomatic infected individuals is the primary means of controlling outbreaks in closed spaces such as schools and military camps. However, the disease is still spreading despite the implementation of control measures. To reveal the underlying mechanism of this phenomenon, we propose a dynamic model that considers invisible transmission and isolated confirmed cases. By calculating and analyzing the control reproduction number, it is found that asymptomatic infected individuals play an important role in the spread of the epidemic. Therefore, in the absence of specific vaccines, non-pharmaceutical interventions such as quarantine of exposed individuals are effective means to mitigate severity. The results show that the earlier the control of invisible transmission is implemented, the lower the peak and the shorter the duration of the outbreak. These findings will provide the theoretical basis and recommendations for prevention and control of human adenovirus transmission in closed spaces.